The U.S. and the Philippines in our image : showcase of democracy [videorecording]. (KCET, 1989)
Asserts the U.S. efforts in suppressing peasant insurgency during the Magsaysay administration. Discusses the usurpation or power and violation of human rights during the marcos regime. Observes a growing anti-American feeling and mounting rebellion during the latter period. Fear of communism in the U.S. spread to its Asian ally and dictatorial repression was sanctioned. This program, documents how continuing economic and political problems have frustrated the Philippine democratic ideal.